Characterization of the groEL and groES Loci in Bifidobacterium breve UCC 2003: Genetic, Transcriptional, and Phylogenetic Analyses - Ventura, Marco (American Society for Microbiology, 2004)
The bacterial heat shock response is characterized by the elevated expression of a number of chaperone complexes, including the GroEL and GroES proteins. The groES and groEL genes are highly conserved among eubacteria and are typically arranged as an operon. Genome analysis of Bifidobacterium breve UCC 2003 revealed that the groES and groEL genes are located in different chromosomal regions. The heat inducibility of the groEL and groES genes of B. breve UCC 2003 was verified by slot blot analysis. Northern blot analyses showed that the cspA gene is cotranscribed with the groEL gene, while the groES gene is transcribed as a monocistronic unit. The transcription initiation sites of these two mRNAs were determined by primer extension. Sequence and transcriptional analyses of the region flanking the groEL and groES genes of various bifidobacteria revealed similar groEL-cspA and groES gene units, suggesting a novel genetic organization of these chaperones. Phylogenetic analysis of the available bifidobacterial groES and groEL genes suggested that these genes evolved differently. Discrepancies in the phylogenetic positioning of groES-based trees make this gene an unreliable molecular marker. On the other hand, the bifidobacterial groEL gene sequences can be used as an alternative to current methods for tracing Bifidobacterium species, particularly because they allow a high level of discrimination between closely related species of this genus.